Reporting of multi-arm parallel-group randomized trials: Extension of the consort 2010 statement - Juszczak, E; Altman, D (American Medical Association, 2019)
Importance: The quality of reporting of randomized clinical trials is suboptimal. In an era in which the need for greater research transparency is paramount, inadequate reporting hinders assessment of the reliability and validity of trial findings. The Consolidated Standards of Reporting Trials (CONSORT) 2010 Statement was developed to improve the reporting of randomized clinical trials, but the primary focus was on parallel-group trials with 2 groups. Multi-arm trials that use a parallel-group design (comparing treatments by concurrently randomizing participants to one of the treatment groups, usually with equal probability) but have 3 or more groups are relatively common. The quality of reporting of multi-arm trials varies substantially, making judgments and interpretation difficult. While the majority of the elements of the CONSORT 2010 Statement apply equally to multi-arm trials, some elements need adaptation, and, in some cases, additional issues need to be clarified. Objective: To present an extension to the CONSORT 2010 Statement for reporting multi-arm trials to facilitate the reporting of such trials. Design: A guideline writing group, which included all authors, formed following the CONSORT group meeting in 2014. The authors met in person and by teleconference bimonthly between 2014 and 2018 to develop and revise the checklist and the accompanying text, with additional discussions by email. A draft manuscript was circulated to the wider CONSORT group of 36 individuals, plus 5 other selected individuals known for their specialist knowledge in clinical trials, for review. Extensive feedback was received from 14 individuals and, after detailed consideration of their comments, a final revised version of the extension was prepared. Findings: This CONSORT extension for multi-arm trials expands on 10 items of the CONSORT 2010 checklist and provides examples of good reporting and a rationale for the importance of each extension item. Key recommendations are that multi-arm trials should be identified as such and require clear objectives and hypotheses referring to all of the treatment groups. Primary treatment comparisons should be identified and authors should report the planned and unplanned comparisons resulting from multiple groups completely and transparently. If statistical adjustments for multiplicity are applied, the rationale and method used should be described. Conclusions and Relevance: This extension of the CONSORT 2010 Statement provides specific guidance for the reporting of multi-arm parallel-group randomized clinical trials and should help provide greater transparency and accuracy in the reporting of such trials.